Origin of B chromosomes in Characidium alipioi (Characiformes, Crenuchidae) and its relationship with supernumerary chromosomes in other Characidium species - Serrano, Erica Alves [UNESP]; Utsunomia, Ricardo [UNESP]; Scudeller, Patricia Sobrinho [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Pensoft Publ, 2017)
B chromosomes are apparently dispensable components found in the genomes of many species that are mainly composed of repetitive DNA sequences. Among the numerous questions concerning B chromosomes, the origin of these elements has been widely studied. To date, supernumerary chromosomes have been identified in approximately 60 species of fish, including species of the genus Characidium Reinhardt, 1867 in which these elements appear to have independently originated. In this study, we used molecular cytogenetic techniques to investigate the origin of B chromosomes in a population of Characidium alipioi Travassos, 1955 and determine their relationship with the extra chromosomes of other species of the genus. The results showed that the B chromosomes of C. alipioi had an intraspecific origin, apparently originated independently in relation to the B chromosomes of C. gomesi Travassos, 1956 C. pterostictum Gomes, 1947 and C. oiticicai Travassos, 1967, since they do not share specific DNA sequences, as well as their possible ancestral chromosomes and belong to different phylogenetic clades. The shared sequences between the supernumerary chromosomes and the autosommal sm pair indicate the origin of these chromosomes.
Keywords: Microdissection; Chromosome painting; FISH; B chromosomes